Quantification of rheumatic mitral stenosis severity with three-dimensional vena contracta area - SAYAR, NURTEN (WILEY, 2019)
Introduction: Rheumatic mitral stenosis (MS) is an important health issue in developing countries. Assessment of the correct mitral valve area (MVA) is essential for the timing of intervention. Most of the parameters for the assessment of rheumatic MS are derived from Two-dimensional (2D) echocardiography. Three-dimensional (3D) echocardiography is commonly used in our daily practice at the present time. The aim of this study was to assess the value of 3D echocardiography mitral valve vena contracta area (VCA) in predicting the severity of Rheumatic MS by comparing 3D planimetry. Methods: The patients, who had been diagnosed as mild, moderate, and severe rheumatic MS with conventional methods (pressure half time, planimetry) by 2D transesophageal echocardiography (TEE)/ transthoracic echocardiography (TTE), underwent 3D TEE evaluation. Also, the patients who had an atrial fibrillation and more than moderate aortic regurgitation were included in the study. 3D TEE full volume mitral valve VCA was measured in end-diastole during its largest dimensions. 3D TEE full volume and 3D zoom MVA planimetry were measured at the end-diastole during the mitral valve's largest opening. Results: We studied 40 patients (the mean age: 51.1 +/- 11.6 years, 31 females) with rheumatic MS. 3D TEE VCA was found to be highly correlated with the 3D TEE MVA (r = 0.82, P < 0.001). Conclusion: Our study findings provide evidence that 3D TEE mitral valve VCA can be additionally used in detecting the severity of rheumatic MS.
Keywords: 3D-echocardiography; mitral stenos's; vena contracta area; MANAGEMENT